Enhancing Public Awareness of Legal Aid Access for Indigent Defendants in Criminal Proceedings - Arfa, Nys.; Lasmadi, Sahuri; Sudarti, Elly; Erwin, Erwin (Jurnal Karya Abdi Masyarakat, 2023)
This community service program was conducted in Maro Sebo Subdistrict, Muaro Jambi Regency, focusing on raising awareness of legal aid rights for underprivileged individuals involved in criminal cases. The program aimed to enhance the public’s understanding of the legal aid services available to economically disadvantaged suspects or defendants and to increase legal consciousness regarding the use of such rights in resolving criminal matters. Based on Article 1 Point 1 of Law No. 6 of 2011 on Legal Aid, legal aid refers to legal services provided free of charge by authorized institutions to recipients who meet certain criteria. The target group of this program includes community members who are potentially subject to criminal prosecution but lack access to legal assistance. Using participatory education methods such as interactive discussions and legal counseling, the program facilitated knowledge sharing between legal experts and residents. As a result, participants demonstrated improved awareness of their legal rights and the procedures to access legal aid. The program contributes to promoting human rights, strengthening the rule of law, and encouraging inclusive access to justice through grassroots legal empowerment initiatives.